Ending The Past: International Law, Intertemporality, and Reparations for Past Wrongs - Rémi Fuhrmann; Melissa Schweizer (German Law Journal)
There has been increasing attention both at national and international level to demands of reparations for historic injustices—colonialism, enslavement and the transatlantic chattel slave trade—and the role and relevance of international law in this context. A routinely identified legal obstacle to reparation demands is the doctrine of intertemporal law, which is generally interpreted to require past acts to be considered in the light of the law contemporary with them. This interpretation of the intertemporal doctrine has been contested more recently in international legal scholarship and practice, which both seek to instill an increased sense of ambiguity into the laws of the past, but crucially, this Article shows, these efforts do not extend this ambiguity to the doctrine of intertemporal law itself. This Article takes a closer look at the intertemporal doctrine and interrogates these varying interpretations. It analyses both conventional and critical international legal scholarship on the intertemporal doctrine in the context of reparation claims for historic injustices and contrasts them to the scholarly reception of the intertemporal doctrine in the past and selected cases from the International Court of Justice (“ICJ”), arguing that whilst an often–unquestioned static understanding of intertemporality prevails, more dynamic interpretations of the doctrine also exist. By building on these legal arguments that enshrine a less static relationship between past and present laws within the discipline of international law—including ICJ decisions, judges’ dissenting opinions, states’ arguments, and critical legal scholarship—the Article defends a potentially emancipatory interpretive approach to the doctrine that could reframe it so as to support, rather than hinder, reparation claims for historic injustices in international law.